Social Change in Postmodern Teacher Education in Nigeria: A Qualitative Analysis of Curriculum and Instructional Strategies - ONIYE, Masud Ibrahim; ABDULLAHI, Musa Siddiq; BADRU, Surajudeen Adewale; ALIYU, Yunus; ALABI, Jimoh Adeniyi (Ilorin Journal of Education, 2024)
This study aimed at addressing how social change described in postmodern teacher education is captured in the curriculum and instructional strategies within the context of Nigerian Undergraduate Teacher Education. A qualitative research approach was employed for generating deeper insights into the phenomena. In the first part of the study, 11 lecturers from 11 universities were interviewed to generate qualitative data. The 11 lecturers were picked through purposive sampling. Thematic method of data analysis was used to analyse the responses gathered from the participants. The result showed formal curriculum does not significantly predict Conceptualization of Teacher Education Goals (CTEG), whereas informal curriculum, formal and informal instruction, overall curriculum, and overall instruction all significantly predict undergraduate teachers’ CTEG, and thus, social change. The study provided important information for policy, curriculum, strategy, and implementation (re)design and/or review in line with postmodern TE that is relevant for the twenty-first century.